Grain dust explosions down in 1991 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Only twelve grain dust explosions were recorded in the U.S. in 1991 according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Marketing and Safety Specialist, Kansas State University. This compares to 15 in 1990 and a ten-year average of 16 explosions.
Keywords: Grain dust; Dust explosions